Clinical relevance of fibrin membranous structures in the intra‐photoreceptor outer segment separation on spectral domain optical coherence tomography (SD‐OCT) in initial‐onset acute Vogt‐Koyanagi‐Harada disease. Issue 3 (11th October 2022) - Motegi, Shuntaro; Nagura, Koichi; Yoneda, Keisuke; Harimoto, Kozo; Sato, Tomohito; Herbort, Carl P.; Takeuchi, Masaru
Abstract: Purpose: The purpose of the study was to investigate clinical relevance of fibrin membranous structure (FMS) in the photoreceptor outer segments on spectral‐domain optical coherence tomography (SD‐OCT) in untreated initial‐onset acute Vogt‐Koyanagi‐Harada (VKH) disease. Methods: Clinical charts of 39 patients (78 eyes) diagnosed with initial‐onset VKH disease were retrospectively reviewed. Age, gender, period from the onset of symptoms to first visit, visual acuity (VA), intraocular pressure (IOP), anterior chamber cells, serous retinal detachment (SRD), SD‐OCT findings, as well as fluorescein (FA), and indocyanine green angiography (ICGA) were collected. Results: FMS was observed in 24 out of 39 VKH patients in either eye (61.5%). VKH patients with FMS (FMS group) were significantly younger and had the shorter period from the onset of symptoms to the first visit compared with those without FMS (non‐FMS group). Mean logMAR VA and proportion of pooling of dye, mean central retinal thickness (CRT) were significantly higher in FMS group than in non‐FMS group. In contrast, hyperfluorescence of the optic disc on FA was more in non‐FMS group than in FMS group. Significant positive correlations between CRT and logMAR VA or IOP were only observed in the FMS group. Total amount of corticosteroids was significantly greater in FMS group than in non‐FMS group. However, there were no significant differences in LogMAR VA and IOP between two groups at 6 months after treatment initiation. Conclusion: FMS on SD‐OCT is a critical feature observed in the early stage of initial‐onset acute VKH disease, which is more common in younger patients and is related to the disease activity.